2020
DOI: 10.1158/0008-5472.can-19-3126
|View full text |Cite
|
Sign up to set email alerts
|

ATM Loss Confers Greater Sensitivity to ATR Inhibition Than PARP Inhibition in Prostate Cancer

Abstract: Alterations in DNA damage response (DDR) genes are common in advanced prostate tumors and are associated with unique genomic and clinical features. ATM is a DDR kinase that has a central role in coordinating DNA repair and cell-cycle response following DNA damage, and ATM alterations are present in approximately 5% of advanced prostate tumors. Recently, inhibitors of PARP have demonstrated activity in advanced prostate tumors harboring DDR gene alterations, particularly in tumors with BRCA1/2 alterations. Howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 29 publications
3
73
0
3
Order By: Relevance
“…Prospective assessment of genomically stratified melanomas that consider mutational signatures may enable recovery of a rarely utilized therapeutic modality (platinum-based chemotherapy) and others not widely considered (e.g. ATR inhibitors 68 , 76 ) for melanoma. Moreover, prospective generation of new melanoma models that captures the genomic and phenotypic diversity of the disease (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective assessment of genomically stratified melanomas that consider mutational signatures may enable recovery of a rarely utilized therapeutic modality (platinum-based chemotherapy) and others not widely considered (e.g. ATR inhibitors 68 , 76 ) for melanoma. Moreover, prospective generation of new melanoma models that captures the genomic and phenotypic diversity of the disease (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous data have suggested that ATM-deficient tumours show an increased sensitivity to PARPi, 47 preclinical findings contradict these reports. 66 Clinical trials conducted in mCRPC patients have shown very limited benefit of PARPi for patients with ATM alterations. 19,[54][55][56][57][58][59] Thus, other strategies should be explored in these patients, and several ATR, ATM and Chk inhibitors either alone or in combination with other agents are at different stages of preclinical or clinical development 67,68 (Table 2).…”
Section: Parpi and Arsimentioning
confidence: 99%
“…ATM inactivation is predicted to inhibit the repair of double-stand DNA breaks, thereby increasing genomic instability and increasing sensitivity to radiation therapy and to platinum-containing drugs, as these therapies induce double-strand breaks [93,94,98]. Although ATM mutated cells were reported to be sensitive to PARP inhibitors in vitro, studies to date have not demonstrated these drugs to be effective in genetic models or in patients with ATM mutations [99,100]. In addition, a number of compounds are now available to target the ATRcheckpoint kinase 1 (Chk1) pathway, including compounds that target ATR and Chk1 (a serine/threonine kinase functioning downstream of ATR), and pancreatic cancers with loss of ATM-mediated DNA repair may show increased sensitivity to one of these [93,94].…”
Section: Atmmentioning
confidence: 99%